Flow cytometry and growth‐based analysis of the effects of fruit sanitation on the physiology of Escherichia coli in orange juice. Issue 3 (7th February 2019) - Anvarian, Amir H. P.; Smith, Madeleine P.; Overton, Tim W.
Abstract: Chlorine‐based solutions are commonly used to sanitize orange fruits prior to juice extraction. We used flow cytometry (FCM) to investigate the physiology of Escherichia coli following its subjection to chlorine‐based solutions and alternative sanitizing agents (H2 O2 and organic acids). Green fluorescent protein (GFP)‐generating E. coli K‐12 were washed with 50–200 ppm available chlorine (AC), 1%–5% H2 O2, 2%–4% citric acid, 4% acetic acid, or 4% lactic acid, after which they were added to 1.2 μm‐filtered orange juice (OJ). Cell physiology was investigated with FCM during storage at 4°C, and culturability was determined using plate counting. Analysis of GFP fluorescence allowed estimation of intracellular pH (pH i ). FCM results demonstrated an inverse relationship between the concentration of AC or H2 O2 and cellular health in OJ. Higher concentrations of sanitizer also resulted in a significantly greater number of viable but nonculturable (VBNC) cells. Real‐time FCM showed that supplementation of AC with 2% citric acid, but not with 100 ppm of Tween‐80, led to a significant reduction in pH i of the cells incubated in OJ, and that the majority of the reduction in pH i occurred during the first 2 min of incubation in OJ. Organic acids were found to be more effective than both AC and H2 O2 in reducing the pH i, viability, and culturability of the cells in OJ. The results confirmed the hypothesis that consecutive subjection of E. coli to maximum legally permitted concentrations of sanitizers and OJ induces the VBNC state. Furthermore, we demonstrate successful application of FCM for monitoring the efficacy of washing procedures. Abstract : Washing fruits prior to production of freshly squeezed fruit juices is a critical control point for food hygiene. Here, we model the washing of oranges and measure the physiology and viability of E. coli to determine which washing treatments decrease viability. We use flow cytometry as a nongrowth‐dependent analysis technique and real‐time flow cytometry to assess rapid changes in cell physiology.